Alloy‐Type Anodes for High‐Performance Rechargeable Batteries. Issue 33 (13th July 2022) - Peng, Manqi; Shin, Kyungsoo; Jiang, Lixia; Jin, Ye; Zeng, Ke; Zhou, Xiaolong; Tang, Yongbing
Abstract: Alloy‐type anodes are one of the most promising classes of next‐generation anode materials due to their ultrahigh theoretical capacity (2–10 times that of graphite). However, current alloy‐type anodes have several limitations: huge volume expansion, high tendency to fracture and disintegrate, an unstable solid–electrolyte interphase (SEI) layer, and low Coulombic efficiency. Efforts to overcome these challenges are ongoing. This Review details recent progress in the research of batteries based on alloy‐type anodes and discusses the direction of their future development. We conclude that improvements in structural design, the introduction of a protective interface, and the selection of suitable electrolytes are the most effective ways to improve the performance of alloy‐type anodes. Furthermore, future studies should direct more attention toward analyzing their synergistic promoting effect. Abstract : Alloy‐type anodes are one of the most promising anodes because of their high energy density, relatively low electrode potential and low cost, but they can also undergo large volume expansion, resulting in disintegration and fracturing of anodes. In this Review useful strategies to solve these problems are discussed including the structural design of anodes, construction of a protective interface on anodes, and selection of suitable electrolytes.